Paul M. Sweezy Monopolio e finanza nella crisi del capitalismo - Cecchi, Amos (Studi e saggi, 2022)
Paul M. Sweezy (New York, 1910-2004) was a co-founder and, for over half a century, co-editor of Monthly Review. At the basis of his theoretical thought there is a Marxian approach, open and creative, and an attention to high elaboration of the twentieth century - Hilferding and Veblen, Schumpeter and Keynes, Kalecki and Steindl. With The Theory of Capitalist Development (1942) and Monopoly Capital (1966, written with Baran), he was a reference point on a global level. Monopoly capitalism is marked by an organic tendency to stagnation. Antagonistic factors can, in some way, counteract it: waste, with induced consumption and armaments, epoch-making innovations and wars. In the Sweezian reflection of the last quarter of the twentieth century - also in dialogue with Minsky - the systemic trend is particularly counteracted by the large indebtedness and finance explosion. However, finance becoming autonomous and placing itself at the center of the system increases its instability and unsustainability and exposure to the crisis.